2021
DOI: 10.3389/fnhum.2021.661079
|View full text |Cite
|
Sign up to set email alerts
|

A Short-Term Intervention of High-Intensity Exercise and Anodal-tDCS on Motor Learning in Middle-Aged Adults: An RCT

Abstract: High-intensity exercise has enhanced motor learning in healthy young adults. Anodal-transcranial direct current stimulation (a-tDCS) may optimize these effects. This study aimed to determine the effects of a short-term high-intensity interval exercise intervention either with or without a-tDCS on the learning and retention of a novel motor task in middle-aged adults. Forty-two healthy middle-aged adults (age = 44.6 ± 6.3, female = 76%) were randomized into three groups: exercise and active a-tDCS, exercise and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Alternatively, given the improvement seen in the exercise group during acquisition, another possible explanation is that the exercise group reached a ceiling of improvement on the SVIPT task, which resulted in reduced opportunity for offline consolidation effects over and above that seen during acquisition. However, ceiling effects are unlikely because the SVIPT has previously been used in multi-day training studies ( Reis et al, 2009 , 2015 ; Quinlan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, given the improvement seen in the exercise group during acquisition, another possible explanation is that the exercise group reached a ceiling of improvement on the SVIPT task, which resulted in reduced opportunity for offline consolidation effects over and above that seen during acquisition. However, ceiling effects are unlikely because the SVIPT has previously been used in multi-day training studies ( Reis et al, 2009 , 2015 ; Quinlan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating the effects of exercise on motor learning in healthy samples have found effects from a single bout. Studies of healthy young adults have indicated benefits of an acute bout of high-intensity exercise on both motor skill acquisition ( Mang et al, 2014 ) and consolidation ( Roig et al, 2012 ; Skriver et al, 2014 ; Stavrinos and Coxon, 2017 ), [although not all, see for example: Pixa et al (2021) , Quinlan et al (2021) ]. In some healthy young adult studies, moderate-intensity exercise has also been shown to facilitate motor learning.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we show that increasing aerobic exercise in middle-aged individuals with a previous exercise regimen can confer additional affective state improvements beyond maintaining an exercise regimen. Though the majority of studies have focused on younger or older populations (Reed and Ones, 2006 ; Chang et al, 2012 ; Hogan et al, 2013 ) and newer research has focused on middle-aged populations (Chen et al, 2019 ; Quinlan et al, 2021 ), our work is some of the first longitudinal exercise research in middle-aged adults. These beneficial effects on affective state are in part thought to be due to exercise-induced increases in neurotrophins and neuromodulators including dopamine, serotonin, norepinephrine, endocannabinoids, and endogenous opioids (Dietrich and McDaniel, 2004 ; Fuss and Gass, 2010 ; Lin and Kuo, 2013 ; Siebers et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies examining the effects of long-term exercise on brain health have been conducted in either children or low fit, elderly populations. Few studies have examined the effects of exercising on psychological state and cognitive health in healthy, moderately fit adults (but see Chen et al, 2019 ; Quinlan et al, 2021 ). In addition, many longitudinal exercise studies examining cognitive functioning are not always focused on increasing cardiorespiratory fitness (VO 2 max) levels (Smiley-Oyen et al, 2008 ; Ruscheweyh et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%